DEEP-SEA mining: Policy options to preserve the last frontier - Lessons from Antarctica's mineral resource convention. (May 2020) - Kirkham, Nicholas R.; Gjerde, Kristina M.; Wilson, A. Meriwether W.
Abstract: Today the International Seabed Authority (ISA), through its member States, is in the process of developing regulations to govern deep-sea mineral mining in areas beyond national jurisdiction, with self-imposed regulatory deadlines of July 2020. Given the complexities of the ISA's dual responsibility to both develop and protect the seabed for all of humanity over time, this article explores to what extent the standards established in the 1988 Convention on the Regulation of Antarctic Mineral Resource Activities (CRAMRA) might guide the ISA through its paradoxical mandate. Principles embraced in CRAMRA include the need for: i) sufficient information to ensure informed decisions, ii) consideration of impacts on dependent and associated seabed ecosystems; iii) requirements for comprehensive and cumulative impact assessments; iv) assurances of technological capacity to monitor key environmental parameters and measure change; v) effective operating procedures for accident responses, and vi) priority use of the precautionary principle. These principles with regard to mineral resource regulation in the icy and fragile Antarctic frontier operationalize the precautionary approach and can generate valuable lessons for regulating the future deep-sea mining industry to protect the remote, dark and similarly fragile deep ocean frontier. Highlights: Antarctic mineral resource regime provides timely solutions to DSM regulations. Need to recognize dependent and associated deep-sea ecosystems in ISA regulations. CRAMRA operationalizes precautionary approach with sufficient information requirement. Framework and function for an independent scientific committee within ISA.